IR and Multi Scale Retinex image Enhancement for Concealed Weapon Detection - Nashwan Jasim Hussein; Fei Hu; Hao Hu; Abdalrazak Tareq Rahem (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
A Concealed Weapon Detection (CWD) had been developed by a large number of researchers and technologies. As a result of the weakness of the infrared images in unique altogether graphic items, infrared and MMW images become inaccurate and insufficient to obviously detectand deal withweaponry objectsin an invisible setting. This article uses Multi Scale Retinex and contrast stretching image processing enhancement techniques to improve the recognition of weapons concealed below attire. Specifically, the focus of the study is on detecting weapons and ammos by enhancing the IR pictures based on image processing techniques. Evaluation techniques were empirically proved to be able to show the enhancement percentage progress.